Pengaruh Suhu Ekstraksi Terhadap Kualitas Alginat Rumput Laut Turbinaria sp. dari Pantai Krakal, Gunung Kidul-Yogyakarta - Wibowo, Arvianto; Ridlo, Ali; Sedjati, Sri (977-2407769)
Turbinaria sp. is a type of brown algae that produce alginate. Alginate is widely used in industry, such as for a coagulant, suspending, stabilizers, film formers, gel formation, and emulsifier. The objective of research was to know the effect of temperature exstraction toward quality of alginate such as yield, water content, ashes content, and viscosity of Turbinaria sp. Sampling of Turbinaria sp. was done in Krakal Beach Gunung Kidul, Yogyakarta. The method used was experimental method. Design experiment applied was Complete Randomized Design (CRD) with Na2CO3 7 % by different Temperature treatment from 40 ºC 50 ºC, 60 ºC, 70 ºC, and 80 ºC of concentration triplicate toward alginate quality. The results showed that the higher temperature exstraction caused higher yield, and lower water content, ashes content, and viscosity. The result showed the highest yield was obtained at temperature 80 ºC (27,96 ± 0,34 %). The lowest water content was obtained at temperature 80 ºC (15,92 ± 0,63 %). The lowest ashes content was obtained at temperature 80 ºC (23,28 ± 2,51 %). The highest viscosity content was obtained at temperature 40 ºC (26,81 ± 1,20 cPs). Treatment temperature 50 ºC produce temperature best if seen from the odor of which set standard.